INFLUENCE OF OCULAR LIQUIDS AND OF HYALURONIC ACID ON METAMORPHOSIS OF THE XOCHIMILCO AXOLOTL - TAPIA, MARCO A; SOTO VERGARA, EDUARDO (Hospital General, CD MEXICO, DF, MEX, 1950)
A method of quantitative analysis of threonine is described Fish (5 species) varied from 675% to 1187% of dry weight; beer yeast (4 varieties) from 212 to 487% dry weight; beans (8 varieties) from 038 to 13%; miscellaneous legume seeds (5 species)
REV SOC MEX HIST NAT
Keywords: INFLUENCE, OCULAR LIQUIDS, HYALURONIC ACID, METAMORPHOSIS, XOCHIMILCO AXOLOTL; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); HERPETOLOGIA